Meta-analysis of indoor temperatures in new-build housing. Issue 1 (17th February 2017) - McGill, Gráinne; Sharpe, Tim; Robertson, Lynette; Gupta, Rajat; Mawditt, Ian
ABSTRACT: Despite growing concerns about overheating, a lack of evidence exists on the scale of the problem, particularly in contemporary UK housing. This paper presents the results of a meta-analysis of indoor temperatures in selected low-energy housing. Temperature data recorded at five-minute intervals in 60 dwellings across 19 demonstration projects (2012–14) were collated and analysed to investigate the prevalence of overheating. Findings evidence high summertime temperatures, with 27% of living rooms exceeding 28°C during August. Based on the Chartered Institution of Building Services Engineers (CIBSE) threshold of 5% annual occupied hours > 25°C, 57% of bedrooms and 75% of living rooms were classified as having overheated. Overall, 30% of living rooms exceeded the adaptive comfort threshold of > 3% occupied hours Δ T  ≥ 1 K. The results suggest a fundamental relationship between ventilation and indoor temperatures. The higher minimum and average summertime temperatures observed in mechanical ventilation with heat recovery (MVHR) homes ( p  < 0.05) and lower temperature range ( p  < 0.001) suggest the need for greater attention to adequate summertime ventilation provision in airtight homes. The results demonstrate a high prevalence of overheating in exemplary housing, indicating the need for greater efforts to ensure the effective implementation of strategies to minimize overheating and improve ventilation in low-energy homes.